Efficacy of Different Antihypertensive Drugs among newly Diagnosed Hypertensive Patient in Dhulikhel Hospital - Humagain, S.; Koju, R. (Kathmandu University Medical Journal, 2017)
Background Cardiovascular disease represents the largest burden on global health, important modifiable risk factor being hypertension. Difference in response to antihypertensive medication depending on ethnic group is well recognized. There is very few data regarding this difference in the South Asian population especially from Nepal.Objective The aim of this study is to find out which antihypertensive medication has better efficacy in our population.Method One seventy two newly diagnosed hypertensive patients who presented to cardiology OPD were included. Blood Pressure (BP) was recorded in both arms at least three times. Patients were counseled for lifestyle and dietary modification and were prescribed one of the three drugs Hydrochlorthiazide 25 mg or Amlodipine 5 mg or Enalapril 5 mg. Patients were called back in 4-6 weeks time and Blood Pressure was recorded in similar manner.Result Out of 172 patients, 97 were male and 75 female. The mean age was 55.49±1.03 years. Mean Systolic BP before treatment was 156.2±10.6 mm of Hg and Mean Diastolic BP before treatment was 100.5 ±6.8 with no statistically significant difference among different groups. However Systolic BP reduction was 14.6 ±5.1, 21.9±5.9 and 21.8±7.4 by Hydrochlorthiazide , Amlodipine and Enalapril respectively. Diastolic BP reduction was 8.8±2.5, 14.2±2.8 and 14.3±2.9 by Hydrochlorthiazide, Amlodipine and Enalapril respectively.Conclusion Amlodipine and Enalapril are equally effective in controlling BP in our population. Hydrochlorthiazide is less effective than both Amlodipine and Enalapril.